Cigarette Smoke Exposure, Pediatric Lung Disease, and COVID-19 - Schiliro, Marta; Vogel, Elizabeth R.; Paolini, Lucia; Pabelick, Christina M. (Frontiers in Physiology, 2021)
The detrimental effects of tobacco exposure on children’s health are well known. Nonetheless, the prevalence of secondhand or direct cigarette smoke exposure in the pediatric population has not significantly decreased over time. On the contrary, the rapid incline in use of e-cigarettes among adolescents has evoked public health concerns since increasing cases of vaping-induced acute lung injury have highlighted the potential harm of these new “smoking” devices. Two pediatric populations are especially vulnerable to the detrimental effects of cigarette smoke. The first group is former premature infants whose risk is elevated both due to their prematurity as well as other risk factors such as oxygen and mechanical ventilation to which they are disproportionately exposed. The second group is children and adolescents with chronic respiratory diseases, in particular asthma and other wheezing disorders. Coronavirus disease 2019 (COVID-19) is a spectrum of diseases caused by infection with the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that has spread worldwide over the last year. Here, respiratory symptoms ranging from mild to acute respiratory distress syndrome (ARDS) are at the forefront of COVID-19 cases among adults. Cigarette smoking is associated with worse outcomes in this population. Interestingly, SARS-CoV-2 infection affects children differently in regard to infection susceptibility, disease manifestations, and complications. Although children carry and transmit the virus, the likelihood of symptomatic infection is low, and the rates of hospitalization and death are even lower when compared to the adult population. However, multisystem inflammatory syndrome is recognized as a serious consequence of COVID-19 infection in the pediatric population. In addition, recent data demonstrate specific clinical patterns in children infected with SARS-CoV-2 who develop multisystem inflammatory syndrome versus severe COVID-19. In this review, we highlight the pulmonary effects of cigarette smoke exposure in vulnerable pediatric populations in the context of the ongoing SARS-CoV-2 pandemic.